Perivalvular Extension of Infective Endocarditis After Transcatheter Aortic Valve Replacement . (11th December 2021) - Panagides, Vassili; del Val, David; Abdel-Wahab, Mohamed; Mangner, Norman; Durand, Eric; Ihlemann, Nikolaj; Urena, Marina; Pellegrini, Costanza; Giannini, Francesco; Gasior, Tomasz; Wojakowski, Wojtek; Landt, Martin; et al.
Abstract: Background: Infective endocarditis (IE) following transcatheter aortic valve replacement (TAVR) has been associated with a dismal prognosis. However, scarce data exist on IE perivalvular extension (PEE) in such patients. Methods: This multicenter study included 579 patients who had the diagnosis of definite IE at a median of 171 (53–421) days following TAVR. PEE was defined as the presence of an intracardiac abscess, pseudoaneurysm, or fistula. Results: A total of 105 patients (18.1%) were diagnosed with PEE (perivalvular abscess, pseudoaneurysm, fistula, or a combination in 87, 7, 7, and 4 patients, respectively). A history of chronic kidney disease (adjusted odds ratio [ORadj ], 2.08; 95% confidence interval [CI]: 1.27–3.41; P  = .003) and IE secondary to coagulase-negative staphylococci (ORadj, 2.71; 95% CI: 1.57–4.69; P  < .001) were associated with an increased risk of PEE. Surgery was performed at index IE episode in 34 patients (32.4%) with PEE (vs 15.2% in patients without PEE, P  < .001). In-hospital and 2-year mortality rates among PEE-IE patients were 36.5% and 69.4%, respectively. Factors independently associated with an increased mortality were the occurrence of other complications (stroke post-TAVR, acute renal failure, septic shock) and the lack of surgery at index IE hospitalization ( p adj  < 0.05 for all). Conclusions: PEE occurred in about one-fifth of IE post-TAVR patients, with the presence of coagulase-negative staphylococci and chronic kidney disease determining an increased risk. Patients with PEE-IE exhibited high early and late mortality rates, and surgery during IE hospitalization seemed to be associated with better outcomes. Abstract : Perivalvular extension was diagnosed in 18.1% of patients with infective endocarditis after transcatheter aortic valve replacement. Chronic kidney disease and coagulase-negative streptococci were risk factors of this serious complication. Surgery was associated with better outcomes.